A case of human dermatitis linked to the infection of Cheyletiella blakei Smiley (Acarina Cheyletiellidae) on Persian cat (Bollettino di zoologia agraria e bachicoltura, 2024)
It is pointed out, for the first time in Italy, a human dermatitis linked to the infestations of the mite Cheyletiella blakei Smiley on a long haired cat. Short notes are given on the cutaneous symptoms of the affected subjects, the mite behaviour and its morphology.